2018
DOI: 10.1002/ece3.4165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rearing conditions on natal dispersal processes in a long‐lived predator bird

Abstract: Natal or prebreeding dispersal is a key driver of the functioning, dynamics, and evolution of populations. Conditions experienced by individuals during development, that is, rearing conditions, may have serious consequences for the multiple components that shape natal dispersal processes. Rearing conditions vary as a result of differences in parental and environmental quality, and it has been shown that favorable rearing conditions are beneficial for individuals throughout their lives. However, the long‐term c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 71 publications
(215 reference statements)
0
8
0
Order By: Relevance
“…Both variables are usually considered as good proxies of individual quality in birds, and indeed have been related to survival prospects later in life 80 , so these females probably decided voluntarily to move further. In addition, body condition may be a prerequisite for not suffering high costs during long-distance movements 81 , and may affect different aspects of the dispersal process related to landscape exploration, such as speed, tortuosity, and path length 82 . In late hatched birds, however, body condition did not appear to influence dispersal, which was shaped instead by the density of breeders in the natal population.…”
Section: Discussionmentioning
confidence: 99%
“…Both variables are usually considered as good proxies of individual quality in birds, and indeed have been related to survival prospects later in life 80 , so these females probably decided voluntarily to move further. In addition, body condition may be a prerequisite for not suffering high costs during long-distance movements 81 , and may affect different aspects of the dispersal process related to landscape exploration, such as speed, tortuosity, and path length 82 . In late hatched birds, however, body condition did not appear to influence dispersal, which was shaped instead by the density of breeders in the natal population.…”
Section: Discussionmentioning
confidence: 99%
“…Field observations were also typically undertaken at particular times of the year (Hardey et al, 2013;Hayhow et al, 2017). In addition, beyond nest building, young large raptors are typically less likely to reach any of the reproductive stages leading to fledging than in their later years or in older birds (Steenhof et al, 1983;Sánchez-Zapata et al, 2000;Pedrini and Sergio, 2001;Whitfield et al, 2004a;Azpillaga et al, 2018;Murgatroyd et al, 2018). Hence our analytical cut-off date could also reduce the availability of field evidence of egg-laying through to fledging, i.e., for young eagles which settled on a territory late in the study period there was a lower likelihood of field recording of reproductive activities beyond nest building.…”
Section: Field Validation Of Territory Occupationmentioning
confidence: 99%
“…When modelling population dynamics, first territory settlement represents recruitment of dispersing birds to the prospective breeding population (Azpillaga et al, 2018) which affects measures of occupied territories and a population's breeding productivity (Hayhow et al, 2017;Steenhof et al, 2017;Gjershaug et al, 2018). Age of first territory settlement (AFTS) is therefore an important variable in understanding several features of large raptor populations, not just NDD estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that in Ningshan County, Crested Ibises often forage in the paddy fields on both sides of the Chang'an River, where most of the nest sites exist. In addition, the natal dispersal of wild Crested Ibises and long‐lived raptors is associated with the distribution pattern of foraging places (Yu et al 2010; Azpillaga et al 2018). Thus, the distribution of foraging sites is one of the most important determinants of Crested Ibis breeding site selection in Ningshan County.…”
Section: Discussionmentioning
confidence: 99%